2019
DOI: 10.1177/0391398819841618
|View full text |Cite
|
Sign up to set email alerts
|

Effects of immediate versus delayed ex-vivo lung perfusion in a porcine cardiac arrest donation model

Abstract: Objective: Ex-vivo lung perfusion is a promising tool to evaluate and recondition marginal donor lungs usually after a cold static preservation. The concept of continuous organ perfusion is supposed to reduce ischemic damage; however, the optimal perfusion protocol has not been established yet. The aim of this study was to compare immediate ex-vivo lung perfusion (I-EVLP) to delayed ex-vivo lung perfusion (D-EVLP) after a certain cold static preservation period on lung function in a large animal model. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 26 publications
3
9
0
Order By: Relevance
“…The evaluation of I-EVLP and D-EVLP groups was similar; even though I-EVLP presented a rise in the wet-dry weight ratio and lightly augmented histological findings, and oxygenation capacity (partial oxygen pressure at FiO 2 of 100%) in both groups was maintained at above-expected values for EVLP lungs [22,23]. Our data matched other studies that found that lungs with D-EVLP maintain pulmonary function in a significant way [12] and showed in a porcine model that EVLP with prior cold static preservation for nine hours is as safe and effective as I-EVLP of donor's lungs procurement [13].…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The evaluation of I-EVLP and D-EVLP groups was similar; even though I-EVLP presented a rise in the wet-dry weight ratio and lightly augmented histological findings, and oxygenation capacity (partial oxygen pressure at FiO 2 of 100%) in both groups was maintained at above-expected values for EVLP lungs [22,23]. Our data matched other studies that found that lungs with D-EVLP maintain pulmonary function in a significant way [12] and showed in a porcine model that EVLP with prior cold static preservation for nine hours is as safe and effective as I-EVLP of donor's lungs procurement [13].…”
Section: Discussionsupporting
confidence: 85%
“…Compliance of lung tissue was comparable in both groups, but a trend to higher Cstat and Cdyn in the I-EVLP group was observed. The slight compliance decrease in D-EVLP may be due to longer hypothermia, which would slow the process of reaching the same lung elasticity as in the I-EVLP group [13]. The PIP remained at the same level in both groups during EVLP, with higher values in D-EVLP; however, in porcine models, PIP is higher compared to human lungs [13], and although there was a significant difference between groups, the Δ peak-plateau was not greater than 5 cm H 2 O. Airway and vascular pressures remained stable for 4 h. All other measured lung functional parameters, in both groups, did not differ.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…3 Steen Solution™ is designed as a modified low potassium dextran solution with 70 g/l human serum albumin as major adjuvant. 5,6 Lungs undergoing ischemia present a typical postischemic reperfusion injury (LIRI). 7 Since primary graft dysfunction (PGD) due to LIRI is common in lung transplantations, the development of a safe and reliable technique preventing LIRI would contribute to the improvement of transplanted lungs.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the composition of the perfusion solution used for EVLP seems to be crucial for EVLP's success. 2,6,7,10,11 The composition of the perfusion solution directly influences colloid osmotic pressure and antioxidative properties to reduce ROS (reactive oxygen species) formation and prevent the organ from excessive reperfusion injury. 2,11 Recent studies have investigated antioxidative properties of Steen Solution TM and discovered a specific downregulation of NOX 2 activity.…”
Section: Introductionmentioning
confidence: 99%